Implementation of Occupational Health and Safety Risk in Muhammadiyah Palembang Hospital During the COVID-19 Pandemic - Ahmad Ghiffari; Syahrul Muhammad; Ardi Artanto; Febri Putri Lintang Sari (Universitas STRADA Indonesia, 2021)
Hospitals are workplaces with multiple hazards that can cause health impacts for employees. On May 12, 2020, at the Muhammadiyah Palembang hospital (RSMP), 21 out of 29 medical personnel tested confirmed positive for COVID-19. It is essential to know how the implementation of K3RS in RSMP contains the pandemic. The cross-sectional descriptive observational with a total sampling method, with samples of the workers of RSMP. The questionnaire to 88 respondents was further univariate analyzed. The results with the category percentage of proper, sufficient, and poor on performing adequate PPE were 19,3%, 65,9%, and 14,8%; on washing hands 0,2%, 72,7%, and 17%; on social distancing 47,7%, 37,5%, and 14,8%, respectively. It is recommended to build sufficient infrastructure to enhance the K3RS program.